2013
DOI: 10.1590/s1519-69842013000100022
|View full text |Cite
|
Sign up to set email alerts
|

Penial morphology in three species of Brazilian Tuco-tucos, Ctenomys torquatus, C. minutus, and C. flamarioni (Rodentia: Ctenomyidae)

Abstract: The present study analyses the glans penis and baculum morphology of three Brazilian tuco-tucos, Ctenomys torquatus Lichtenstein, 1830, Ctenomys minutus Nehring, 1887 and Ctenomys flamarioni Travi, 1981, in order to identify possible variations and understand some more about this taxonomically complex group. We used fixed penis from 15 previously listed adult specimens. For a more detailed baculum analysis, the penis underwent dissection and diaphanisation, whereas to analyse the glans penis surface we used Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Structures inherent to the secondary bone tissue were observed, such as the organization of collagen fibers in lamellae, characteristic of long bones, with Haversian systems closely connected to Volkmann channels (Banks, 1992; Junqueira and Carneiro, 2015) in addition to evidence of the organ's characteristic eosinophilia. The findings regarding the presence of the baculum are similar to those of Martucci et al (2011) and as expected when comparing the microstructure to those of canine and domestic feline baculums, as well as some rodent species, although the spoon shape was a unique finding (Rocha‐Barbosa et al, 2013). The baculum was found microscopically in Micomarcai but non‐ossified (Siqueira et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Structures inherent to the secondary bone tissue were observed, such as the organization of collagen fibers in lamellae, characteristic of long bones, with Haversian systems closely connected to Volkmann channels (Banks, 1992; Junqueira and Carneiro, 2015) in addition to evidence of the organ's characteristic eosinophilia. The findings regarding the presence of the baculum are similar to those of Martucci et al (2011) and as expected when comparing the microstructure to those of canine and domestic feline baculums, as well as some rodent species, although the spoon shape was a unique finding (Rocha‐Barbosa et al, 2013). The baculum was found microscopically in Micomarcai but non‐ossified (Siqueira et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…This family is of interest with respect to SSD and sexual selection for two main reasons: first, these rodents are polygynic, a factor that promotes high SSD. The polygynic nature of tuco-tucos' mating system has been revealed by studies of male-male contests, sperm competition, testis size, and penial morphology (Zenuto et al, 1999a,b;Graziani and Lacey, 2004;Bidau and Medina, 2013;Rocha-Barbosa et al, 2013). Second, it has been also shown that their large size variation exhibits a converse Bergmannian pattern along the distribution of the genus (Medina et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…According to Rocha-Barbosa et al (2013), complex penises and ornamentations, like spines, can have several functions, such as inducing ovulation through vaginal stimulation. This stimulation is caused by the friction of the penile spines on the vaginal wall.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several authors have shown the effectiveness of external penile features to differentiate mammals' species that are very close morphologically (e.g., Rocha-Barbosa et al 2013;Cserkész et al 2016Cserkész et al , 2019Comelis et al 2018;Fasel et al 2020). In the past, phallic apparatus morphology was of importance in the systematics of mammals, giving information on the interrelationship of species (Hooper 1958;Lidicker 1968;Balbontin et al 1996).…”
Section: Introductionmentioning
confidence: 99%